Continuous aspirin use does not increase post-endoscopic dissection bleeding risk for gastric neoplasms in patients on antiplatelet therapy - Tounou, Shigetaka; Morita, Yasushi; Hosono, Tomohiro (Endoscopy International Open, 2015)
Background and study aims: Discontinuation of all antiplatelet agents before endoscopic procedures may cause serious complications in some patients. The aim of this study was to evaluate the hemorrhagic risk of post-endoscopic submucosal dissection (ESD) in patients on antiplatelet therapy (APT).Patients and methods: The subjects were 350 patients (377 lesions) who underwent gastric ESD between January 2007 and July 2013. The patients were categorized based on antiplatelet therapies. The primary outcome was post-ESD bleeding. Multivariate analysis was performed to identify independent risk factors for post-ESD bleeding.Results: The patients were categorized into three groups: (1) no APT, 261 patients with 281 lesions; (2) single APT, 58 patients with 63 lesions (53 patients with low dose aspirin [LDA] and 5 patients with a thienopyridine); and (3) dual APT (DAPT), 31 patients with 33 lesions (DAPT with LDA and a thienopyridine). Post-ESD bleeding occurred in 16 of 261 patients in the no APT group (6.1 %), 9 of 58 patients in the single APT group (15.5 %), and 11 of 31 patients in the DAPT group (35.5 %). In multivariate analysis with a Cox proportional hazards model in the no APT and single APT groups, APT (HR 2.7, 95 %CI 1.1 – 6.6, P = 0.03) and diameter of the resected specimen of 40 mm or greater (HR 2.7, 95 %CI 1.2 – 5.9, P = 0.01) were significant risk factors for post-ESD bleeding. In multivariate analysis in the no APT and DAPT groups, DAPT was the only significant risk factor for post-ESD bleeding (HR 16.3, 95 %CI 3.4 – 78.2, P < 0.01). Continuous LDA was not a significant risk factor for post-ESD bleeding in both analyses (HR 0.8, 95 %CI 0.2 – 3.6, P = 0.72 in the no APT and single APT groups; HR 1.0, 95 %CI 0.2 – 5.1, P = 0.95 in the no APT and DAPT groups). Conclusions: APT increased the risk for post-ESD bleeding, and DAPT markedly increased the risk for bleeding. Continuous LDA did not produce an additional hemorrhagic risk in all patients treated with APT. Thus, patients treated with APT should be careful monitored for post-ESD bleeding, and LDA should not be interrupted in patients with a high thromboembolic risk.